2002
DOI: 10.1002/ijc.10620
|View full text |Cite
|
Sign up to set email alerts
|

Automated diagnosis of pigmented skin lesions

Abstract: Since advanced melanoma remains practically incurable, early detection is an important step toward a reduction in mortality. High expectations are entertained for a technique known as dermoscopy or epiluminescence light microscopy; however, evaluation of pigmented skin lesions by this method is often extremely complex and subjective. To obviate the problem of qualitative interpretation, methods based on mathematical analysis of pigmented skin lesions, such as digital dermoscopy analysis, have been developed. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(91 citation statements)
references
References 35 publications
4
83
2
1
Order By: Relevance
“…In the present study, among females the most common lesion was benign melanocytic nevi 17 (54.8%) which was similar to observations of Schafer et al 7 Nevi are benign melanocytic tumours that have cosmetic significance and may act as stimulants or precursors to melanoma. 8 In male's nevus sebaceous was most common lesion 5 (38.5%) which was similar to Rubegni et al, Rajesh et al 1,9 Majority of these lesions were situated on the face 29 (65.9%) and were similar to Rajesh et al In present study, it was observed that malignant melanoma was seen in 2 cases and both were females, which was comparable to other studies. 1,10 but dissimilar to the observations of KORA survey.melanoma is an aggressive tumour, its incidence in India is uncommon when compared to the West.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, among females the most common lesion was benign melanocytic nevi 17 (54.8%) which was similar to observations of Schafer et al 7 Nevi are benign melanocytic tumours that have cosmetic significance and may act as stimulants or precursors to melanoma. 8 In male's nevus sebaceous was most common lesion 5 (38.5%) which was similar to Rubegni et al, Rajesh et al 1,9 Majority of these lesions were situated on the face 29 (65.9%) and were similar to Rajesh et al In present study, it was observed that malignant melanoma was seen in 2 cases and both were females, which was comparable to other studies. 1,10 but dissimilar to the observations of KORA survey.melanoma is an aggressive tumour, its incidence in India is uncommon when compared to the West.…”
Section: Discussionsupporting
confidence: 89%
“…Physician uses this technique for diagnosis of skin cancer more efficiency. The historical researches have proved that ELM can improve the diagnostic accuracy by 5 -30% compare to traditional imaging [2]. Furthermore, ELM has evolution and digitalize that can be used to classification with computer.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the study of Manousaki et al, (2006), has evaluated geometry, color and texture, reaching only 60.9% of sensitivity and specificity of 95.4%. Rubegni et al (2002) have evaluated geometry, color, texture and color Islands, achieving sensitivity and specificity of 94%. The method proposed by Iyatomi et al, (2008) peaked sensitivity and specificity of 86%, based on ABCD rule.…”
Section: Introductionmentioning
confidence: 99%